The Clinical Efficiency and the Mechanism of Sanzi Yangqin Decoction for Chronic Obstructive Pulmonary Disease. (11th June 2021) - Wang, Mengqi; Gu, Wenwen; Kui, Fuguang; Gao, Fan; Niu, Yuji; Li, Wenwen; Zhang, Yaru; Guo, Lijuan; Geng, Shengnan; Du, Gangjun
Abstract : This work is carried out to evaluate the clinical efficacy of Sanzi Yangqin decoction (SZYQD) treating chronic obstructive pulmonary disease (COPD) and to analyze its mechanism. The clinical efficacy of SZYQD treating COPD was evaluated by meta-analysis, and its mechanism was analyzed by network pharmacology. Molecular docking validation of the main active compounds and the core targets was performed by AutoDock vina software. A cigarette smoke (CS) and LPS-induced COPD model in ICR mice was constructed to confirm the effects of luteolin on COPD. Results showed that SZYQD has a greater benefit on the total effect (OR = 3.85, 95% CI [3.07, 4.83], P = 1 ) in the trial group compared with the control group. The percentage of forced expiratory volume in one second (FEV1%) (MD = 0.5, 95% CI [0.41, 0.59], P < 0.00001 ) and first seconds breathing volume percentage of forced vital capacity (FEV1%/FVC) were improved (MD = 5.97, 95% CI [3.23, 8.71], P < 0.00001 ). There are 27 compounds in SZYQD targeting 104 disease targets related to COPD. PPI network analysis indicated that EGFR, MMP9, PTGS2, MMP2, APP, and ERBB2 may be the core targets for the treatment of COPD. Molecular docking demonstrated that luteolin in SZYQD showed the strongest binding activity to core targets. Experimental results revealed that the expression of COPD-related targets in lung tissue was significantly increased in the COPD group and was improved in the luteolin group. Our data indicated that SZYQD has a curative effect on COPD and luteolin is a candidate compound for COPD treatment by regulating EGFR, MMP9, PTGS2, MMP2, APP, and ERBB2.